2010
DOI: 10.1161/strokeaha.110.592360
|View full text |Cite
|
Sign up to set email alerts
|

Functional Occurrence of the Interaction of Tissue Plasminogen Activator With the NR1 Subunit of N -Methyl- d -Aspartate Receptors During Stroke

Abstract: Background and Purpose-Despite its fibrinolytic effect, tissue-type plasminogen activator (tPA) displays deleterious effects in the brain, including proexcitotoxicity, that can reduce the overall benefit from thrombolysis during stroke. We have proposed that tPA potentiates excitotoxicity by interacting with and cleaving the aminoterminal end of the NR1 subunit of N-methyl-D-aspartate receptors, leading to an increased calcium influx, Erk1/2 activation, and neurotoxicity. Because this mechanism is debated, our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 25 publications
(42 reference statements)
1
27
0
Order By: Relevance
“…Importantly, these antibodies do not alter NMDA-induced basal neurotransmission (toxicity, calcium influx), but they specifically block the potentiating effect of tPA on these receptors. Accordingly, we have shown that this strategy of blockage of the tPA/GluN1 interaction leads to behavioral deficits in Swiss mice and also prevents the pro-neurotoxicity of tPA both in vitro and in vivo (Benchenane et al, 2007;Macrez et al, 2010). In addition, in recent studies, we evidenced both in vitro and in vivo that the pro-neurotoxic effect of tPA was mediated by GluN2D subunitcontaining NMDAR (Baron et al, 2010;Jullienne et al, 2011), suggesting that, although tPA interacts with the GluN1 subunit, this mechanism occurs preferentially in GluN2D subunitcontaining NMDAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, these antibodies do not alter NMDA-induced basal neurotransmission (toxicity, calcium influx), but they specifically block the potentiating effect of tPA on these receptors. Accordingly, we have shown that this strategy of blockage of the tPA/GluN1 interaction leads to behavioral deficits in Swiss mice and also prevents the pro-neurotoxicity of tPA both in vitro and in vivo (Benchenane et al, 2007;Macrez et al, 2010). In addition, in recent studies, we evidenced both in vitro and in vivo that the pro-neurotoxic effect of tPA was mediated by GluN2D subunitcontaining NMDAR (Baron et al, 2010;Jullienne et al, 2011), suggesting that, although tPA interacts with the GluN1 subunit, this mechanism occurs preferentially in GluN2D subunitcontaining NMDAR.…”
Section: Discussionmentioning
confidence: 99%
“…Because we have identified the exact location of the interaction of tPA within GluN1 in cultured cortical neurons (Fernández-Monreal et al, 2004), we performed active immunization leading to the production of antibodies recognizing the ATD of GluN1 (Benchenane et al, 2007;Macrez et al, 2010). Importantly, these antibodies do not alter NMDA-induced basal neurotransmission (toxicity, calcium influx), but they specifically block the potentiating effect of tPA on these receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In neurons, tPA can trigger cell signaling through a direct interaction with the NMDA-R, independently of LRP1 (Nicole et al, 2001;Macrez et al, 2010;Ng et al, 2012;Mantuano et al, 2013). To determine whether the NMDA-R signals in response to tPA, independently of LRP1 in Schwann cells, we treated Schwann cells with 12 nM EI-tPA in the presence or absence of RAP for up to 60 min.…”
Section: Nmda-r Is Necessary For Lrp1 Signaling In Schwann Cellsmentioning
confidence: 99%
“…LRP1 ligands have been implicated in neuronal survival (Hayashi et al, 2007;Fuentealba et al, 2009) and in neurite outgrowth (Mantuano et al, 2008a,b;Shi et al, 2009;Yoon et al, 2013). Unlike other LRP1 ligands, tPA interacts directly with the NMDA-R, independently of LRP1, triggering cell signaling, albeit with delayed kinetics (Nicole et al, 2001;Macrez et al, 2010;Ng et al, 2009;Mantuano et al, 2013). NR1 subunit cleavage is reported to be involved in the mechanism by which tPA activates the NMDA-R; however, NR1 cleavage might not be necessary (Nicole et al, 2001;Mantuano et al, 2008a,b).…”
Section: Introductionmentioning
confidence: 99%